Impacts of East Mediterranean Gas Forum on the Energy Security - DÖŞLÜ, SENA (İstanbul Kültür Üniversitesi, 2023)
For centuries, the Eastern Mediterranean has been one of the world's most important strategic transit routes. In today's modern world, the situation is the same; there are many conflicts between the countries in the Eastern Mediterranean region. In this thesis, the regional disputes and conflicts are analyzed focusing on the East Mediterranean Gas Forum. The problems of countries today are different from those of the past. Considering the regional problems, it is understood that energy security is one of the critical problems. Energy security and recent natural gas discoveries are important issues of the Eastern Mediterranean region. This thesis focuses on the impact of the East Mediterranean Gas Forum on energy security. The liberal institutionalism theory used in the thesis is the most appropriate theory to explain the historical developments and evolution of the East Mediterranean Gas Forum. It is analyzed whether the East Mediterranean Gas Forum impacts Europe's ability to overcome its energy crisis. In this study, the impact of the development of the East Mediterranean Gas Forum on the European energy crisis is explained. The East Mediterranean Gas Forum which is an international organization will be effective in solving the European energy crisis. It will be strengthened in its cooperation with Türkiye. Conflicts related to energy security will be able to be solved with Türkiye's involvement in the cooperation process in the region and with its bilateral agreements. In addition, if the parties agree on the necessary conditions, it will be possible to end the conflicts. Improvement of bilateral relations between Türkiye and regional countries will strengthen cooperation in the Eastern Mediterranean. The thesis also analyzes the development of the East Mediterranean Gas Forum over the years and explains the roles played by the member countries in this process. The Republic of Türkiye is not a member of this forum. This thesis focuses on the regional energy security implications and contributions of the East Mediterranean Gas Forum and Türkiye. As an influential actor in the region, Türkiye's relations with Israel, Greece, and Egypt, the East Mediterranean Gas Forum members, are analyzed. The relations among the countries in the Eastern Mediterranean are analyzed from a historical perspective. The energy security in the Eastern Mediterranean can be accomplished with multilateral cooperation among the member states of the East Mediterranean Gas Forum and with the help of Türkiye's involvement in this cooperation process.
Doğu Akdenı̇z Gaz Forumu'nun Enerjı̇ Güvenlı̇ğı̇ Üzerı̇ndekı̇ Etkı̇lerı̇
▪ Yüksek lisans tezi.
Keywords: Eastern Mediterranean; East Mediterranean Gas Forum; Natural Gas; Energy Security; Energy Crisis; Cooperation; Liberal institutionalism; Türkiye; Israel; Egypt; Greece